Solution Structure and Dynamics of the I214V Mutant of the Rabbit Prion Protein - Wen, Yi (Public Library of Science, 2010)
BACKGROUND: The conformational conversion of the host-derived cellular prion protein (PrP(C)) into the disease-associated scrapie isoform (PrP(Sc)) is responsible for the pathogenesis of transmissible spongiform encephalopathies (TSEs). Various single-point mutations in PrP(C)s could cause structural changes and thereby distinctly influence the conformational conversion. Elucidation of the differences between the wild-type rabbit PrP(C) (RaPrP(C)) and various mutants would be of great help to understand the ability of RaPrP(C) to be resistant to TSE agents. METHODOLOGY/PRINCIPAL FINDINGS: We determined the solution structure of the I214V mutant of RaPrP(C)(91–228) and detected the backbone dynamics of its structured C-terminal domain (121–228). The I214V mutant displays a visible shift of surface charge distribution that may have a potential effect on the binding specificity and affinity with other chaperones. The number of hydrogen bonds declines dramatically. Urea-induced transition experiments reveal an obvious decrease in the conformational stability. Furthermore, the NMR dynamics analysis discloses a significant increase in the backbone flexibility on the pico- to nanosecond time scale, indicative of lower energy barrier for structural rearrangement. CONCLUSIONS/SIGNIFICANCE: Our results suggest that both the surface charge distribution and the intrinsic backbone flexibility greatly contribute to species barriers for the transmission of TSEs, and thereby provide valuable hints for understanding the inability of the conformational conversion for RaPrP(C).